Delia, Jackson County - Kirmer, Richard (Kansas State University, The Chapman Center for Rural Studies, 2012)
This study of Delia, Kansas in Jackson County uses photographs, personal interviews, and field research.
Richard Kirmer, “Delia, Jackson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/131.
Keywords: Bohemian; Cunningham; Jsckson County; Ladies Aid Society; Czech; Rossville